To the Land and Beyond: Crab Microbiomes as a Paradigm for the Evolution of Terrestrialization - Cannicci, Stefano; Fratini, Sara; Meriggi, Niccolò; Bacci, Giovanni; Iannucci, Alessio; Mengoni, Alessio; Cavalieri, Duccio (Frontiers in Microbiology, 2020)
The transition to terrestrial environments by formerly aquatic species has occurred repeatedly in many animal phyla and lead to the vast diversity of extant terrestrial species. The differences between aquatic and terrestrial habitats are enormous and involved remarkable morphological and physiological changes. Convergent evolution of various traits is evident among phylogenetically distant taxa, but almost no information is available about the role of symbiotic microbiota in such transition. Here we suggest that intertidal and terrestrial brachyuran crabs are a perfect model to study the evolutionary pathways and the ecological role of animal-microbiome symbioses, since their transition to land is happening right now, through a number of independent lineages. The microorganisms colonizing the gut of intertidal and terrestrial crabs are expected to play a major role to conquer the land, by reducing water losses and permitting the utilization of novel food sources. Indeed, it has been shown that the microbiomes hosted in the digestive system of terrestrial isopods has been critical to digest plant items, but nothing is known about the microbiomes present in the gut of truly terrestrial crabs. Other important physiological regulations that could be facilitated by microbiomes are nitrogen excretion and osmoregulation in the new environment. We also advocate for advances in comparative and functional genomics to uncover physiological aspects of these ongoing evolutionary processes. We think that the multidisciplinary study of microorganisms associated with terrestrial crabs will shed a completely new light on the biological and physiological processes involved in the sea-land transition.